Upaya Meningkatkan Kemampuan Motorik Haluk Melalui Metode Mewarnai Gambar pada Kelompok A RA Muslimat Hidayatush Shibyan - Siti Badrikah; Muslimin Muslimin (Alzam: Journal of Islamic Early Childhood Education, 2021)
This study aims to determine the fine motor development of early childhood group A RA Muslimat Hidayatush Shibyan Cendoro. This type of research is a collaborative classroom action research. The research data were collected using several techniques, such as observation and documentation. The less varied fine motor stimulation was in the use of crayons and markers for coloring activities. The solution given by the author to overcome the problems found in RA Muslimat Hidayatush Shibyan Cendoro group A is to provide a variety of coloring pictures. To achieve maximum fine motor skills with Very Good Development (BSB) criteria vary according to the stage of development so that in the results of observations made in pre-action, cycle I and cycle II each result achieved by the child is also different. Learning to color pictures of group A RA Muslimat Hidayatush Shibyan is very appropriate for developing fine motor skills of group A children of RA Muslimat Hidayatush Shibyan, because through coloring activities children learn about the initial ability to write, namely from the ability to hold coloring tools, move the wrist and hand eye coordination. useful for the next level of education.